Determinants of passenger loyalty in multi-airport regions: Implications for tourism destination - Bezerra, George C. L. (2019)
This study examines the drivers of passenger loyalty to the airport in a multi-airport region. For this purpose, partial least squares–structural equation modelling (PLS–SEM) was used to analyse survey data. The findings highlight the role of customer segmentation to define marketing and operational strategies, which should be used to strengthen the loyalty to the airport as well as to contribute to the improvement of the tourism destination image. In addition, this research offers an integrative approach to analyse passenger perceptions and attitudes regarding the airport experience. This integrative approach can also help airport managers to design and implement more effective performance measurement systems, which could be used to transform the airport environment in a tourism experience.